"Not My Will But Yours be Done": The Use of the Mercy Seat in Theodramatic Perspective. (September 2021) - Couchman, Adam
The "Mercy Seat" performs an important function within Salvation Army worship. It symbolizes the central theological tenet of the immediacy of grace to all. Historically, its function was intended for use by those intending to "receive Christ" for the first time. Over time, its use has broadened to include other intentions whilst simultaneously diminishing in the frequency of its use. This article suggests that when viewed from a theodramatic perspective, the act of praying at the Mercy Seat becomes a contemporary, and improvised, performance of Christ's Gethsemane prayer, "Not my will, but yours be done" (Luke 22:42). The broadening of the understanding of this act to become a deliberately repeated and embodied performance of Jesus' prayer may help to overcome the loss of use of this symbol. Drawing upon the work of Adrienne von Speyr and Kevin Vanhoozer, this article will demonstrate how the prayer of Christ in Gethsemane is embodied through contemporary, improvised performance of his prayer at the Mercy Seat by Salvationists and those new to the faith alike.